Rehabilitation among individuals experiencing homelessness and traumatic brain injury: A scoping review - Chan, Vincy; Estrella, Maria Jennifer; Baddeliyanage, Richelle; Shah, Riya; Babineau, Jessica; Colantonio, Angela (Frontiers in Medicine, 2022)
Traumatic brain injury (TBI) is disproportionately prevalent among individuals experiencing homelessness. While rehabilitation is critical to facilitating recovery after TBI, there is currently limited information on the extent to which rehabilitation is provided to individuals experiencing homelessness and TBI. If unaddressed, this knowledge gap can perpetuate TBI-related challenges and contribute to a repetitive cycle of TBI and homelessness. This scoping review explored the extent to which rehabilitation, including the types of rehabilitation interventions, are available to, or used by, individuals experiencing homelessness and TBI. A systematic search of electronic databases (MEDLINE, Embase, Cochrane CENTRAL Register of Clinical Trials, CINAHL, APA PsycINFO, Applied Social Sciences Index and Abstracts, and Proquest Nursing and Allied Health) was conducted to identify peer-reviewed articles that met predetermined eligibility criteria. Gray literature and reference lists of eligible articles were also searched for relevant content. A descriptive numerical summary of extracted data was conducted, and qualitative analytic techniques were applied to analyze the data. Fifteen peer-reviewed articles and three gray literature reports were included, describing interventions for individuals experiencing homelessness and TBI (N = 4), rehabilitation for individuals experiencing homelessness without specific inclusion criteria for TBI (N = 11), and rehabilitation interventions that included individuals experiencing homelessness and TBI, without specific inclusion criteria for experiences of homelessness or TBI (N = 3). This review demonstrates that rehabilitation programs or interventions for this population already exist, and those that are focused on individuals experiencing homelessness are already serving individuals with TBI. Findings highlight opportunities to adapt existing rehabilitation for individuals who experience homelessness and TBI through screening for TBI, conducting cognitive and functional assessments, and tailoring interventions with multidisciplinary teams. Education and training for healthcare professionals working with individuals experiencing homelessness and TBI should be explored, including structured education and training, collaboration with a multidisciplinary team, and co-development of educational materials with service users. Research that considers the rehabilitation needs of diverse individuals experiencing homelessness and TBI is urgently needed.